919Step-by-step guidance on prospective meta-analyses. (2nd September 2021) - Seidler, Anna Lene; Hunter, Kylie; Cheyne, Saskia; Berlin, Jesse; Ghersi, Davina; Askie, Lisa
Abstract: Focus of Presentation: In a prospective meta-analysis (PMA), studies are included before their results are known. This can reduce risk of publication bias and selective outcome reporting, and enables researchers to harmonise their research efforts. Despite rising numbers, there is little guidance on how to conduct PMA. We, the Cochrane PMA Methods Group, developed step-by-step guidance based on a scoping review, and expert opinions and experiences. Each step is illustrated with a recent case study. Findings: We describe seven steps for conducting PMA. After developing a protocol (Steps 1), a systematic search for eligible planned/ongoing studies should be conducted, including a search of registries, medical databases and contacting stakeholders (Step 2-3). These studies are then invited to form a collaboration (Step 4), ideally including a steering and data analysis committee. Next, important study features such as common core outcomes and confounders are agreed upon (Step 5). This reduces heterogeneity and increases the number of available outcomes for meta-analysis. Certainty of evidence is assessed by adapting tools such as GRADE (Step 6). Results should be reported using adapted versions of reporting tools such as PRISMA (Step 7). Conclusions/Implications: PMA reduce many problems of traditional retrospective systematic reviews and meta-analysis. Updated guidance and recent technical advances will help increase their numbers further. Key messages: PMA are 'next generation systematic reviews' that allow for greatly improved use of data, whilst reducing bias and research waste. This step-by-step guidance will enable more researchers to conduct successful PMA.